Implementasi Pendidikan Multikultural Di Madrasah Aliyah Darussalam Sengkubang - Hafid, Ikhsan; Mustofa, Ali (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to analyze the implementation of multicultural education at MA Darussalam Sengkubang, a madrasah inhabited by students from various ethnic and cultural backgrounds. The method used in this study is a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation studies. The results of the study indicate that multicultural education is implemented through integration in subjects such as Citizenship Education and Social Sciences, as well as in self-development activities, both programmed such as extracurricular and unprogrammed such as morning prayers and national commemoration ceremonies. Supporting factors for the implementation of multicultural education include a school climate that accepts diversity, the role of teachers, and supporting facilities and infrastructure. However, there are several obstacles such as the lack of learning media about diversity, individual attitudes that are less open to differences, and minimal socialization for teachers. Efforts to overcome these obstacles are carried out by instilling values ??of tolerance and respect for differences through school policies, adding educational media, and increasing socialization for teachers and students. This study recommends improving supporting facilities for multicultural education and special training for teachers so that they are able to integrate the concept of multiculturalism effectively in learning.